Embodied valuation: Directional action is associated with item values. Issue 8 (August 2018) - Green, Danielle J; Harris, Alison; Young, Aleena; Reed, Catherine L
We have a lifetime of experience interacting with objects we value. Although many economic theories represent valuation as a purely cognitive process independent of the sensorimotor system, embodied cognitive theory suggests that our memories for items' value should be linked to actions we use to obtain them. Here, we investigated whether the value of real items was associated with specific directional movements toward or away from the body. Participants priced a set of food items to determine their values; they then used directional actions to classify each item as high- or low-value. To determine if value is linked to specific action mappings, movements were referenced either with respect to the object (push toward high-value items; pull away from low-value items) or the self (pull high-value items toward self; push low-value items away). Participants who were assigned (Experiment 1) or chose (Experiment 2) to use an object-referenced action mapping were faster than those using a self-referenced mapping. A control experiment (Experiment 3) using left/right movements found no such difference when action mappings were not toward/away from the body. These results indicate that directional actions toward items are associated with the representation of their value, suggesting an embodied component to economic choice.